IMPLEMENTASI MODEL PEMBELAJARAN LEARNING CYCLE 5E PADA MATERI HIDROLISIS GARAM DI KELAS XI MIPA SMAN 1 BENGKULU TENGAH TAHUN AJARAN 2018/2019 - Isnaini Safitri; Dewi Handayani; Salastri Rohiat (ALOTROP, 2019)
This study aims to determine the effect of the implementation of the 5E Learning Cycle learning model on increasing mastery of concepts in the subject matter of salt hydrolysis. This research was conducted at SMAN 1 Bengkulu Tengah in the 2018/2019 class XI MIP academic year in one meeting. The trial implementation of the 5E Learning Cycle model uses a pre-experimental research design with the form of one-group pretest-posttest design. The study was  conducted in February 2019 at SMAN 1 Bengkulu Tengah. The population in this study were students of class XI MIPA in SMA Negeri 1 Bengkulu Tengah academic year 2018/2019 which amounted to 126 people. Determination of the study sample was carried out by testing the normality of the population. The study sample was taken using simple random sampling technique obtained by students of class XI MIPA 1, the number of students was 31 people. The instruments used consisted of student response questionnaire sheets and concept mastery assessment sheets. Student response data, mastery of concepts were analyzed descriptively and their improvement was analyzed by analysis of gain scores. The results showed that students gave a positive response to the 5E learning cycle model with an average value of 4.2 from a maximum value of 5 which indicated that students felt greatly helped by learning with the 5E Learning Cycle model. This is also supported by a high score increase on mastery of concepts which obtained an average value of 76.97 which is in the effective category. Based on the results of the study, it was concluded that the implementation of the 5E learning cycle model in the subject matter of effective salt hydrolysis to improve mastery of concepts in class XI MIPA SMAN 1 Bengkulu Tengah Academic Year 2018/2019.